Finance banks and ways to improve them in Kazakhstan - Artakshinova, V.; Domnikov, A.Yu. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
In the article the development of the bank, as well as improvement of its activities both for the banks and for the country's population are considered. The aim of banks is to reach a fundamentally new level of business and gain competitive advantages which contributes to the creation of a balanced analytical system for managing cash flows. Banks accumulate the main share of credit resources and provide the clients with a full range of financial services, including loans, deposits, settlement services, purchase and sale, and safekeeping of securities. Therefore, it is necessary to control the receipt and expenditure of funds in order to determine the financial condition of the bank. The development of the banks should follow the path of the overall development of the entire banking system in Kazakhstan with the obligatory consideration of local features of economic development. In this regard, it is essential to improve the role of banks and other credit institutions in measures to stabilize the economy. For Kazakhstani banks in the current economic situation, the issue of profitable investment of the population’s funds and the services of banks in lending specifically in national currency become very relevant. Banking activity is the subject to numerous risks, the underestimation of which can lead to disruptions in work and bankruptcy of credit institutions, causing negative effect to the customers and shareholders. The role of specific banking operations is the basis for assessing the position of the bank in the future.
Банктердің қаржысы жəне оларды жақсарту жолдары
Финансы банков и пути их улучшения в Казахстане
Keywords: finance; bank; deposit; loan; deposit market; banking sector; financial sector; loan portfolio; capital; household deposits